Case Report: Acute Unilateral Uveitis Induced by Infusion of Zoledronic Acid - Kadir Songür; Deniz Başcıllar; Özlem El (Galenos Yayinevi, 2022)
Bisphosphonates are a group of drugs that inhibit osteoclast-mediated bone resorption, used for treating osteoporosis, Paget's disease, metastatic bone disease, and hypercalcemia caused by malignancy. Zoledronic acid treatment, which is the most potent member of the group and is administered annually, is frequently preferred due to high patient compliance. The most common side effect in the first 3 days after administration is transient flu-like syndrome, which has also been reported to cause serious ocular adverse events. Although the most common ocular side effect is nonspecific conjunctivitis, it can also cause serious symptoms such as uveitis and scleritis. A limited number of cases diagnosed as uveitis triggered by zoledronic acid have been reported in the literature. In this article, we presented the occurrence of unilateral anterior uveitis 24 h after the application in a 62-year-old female patient who was under oral letrozole therapy for breast cancer diagnosed previously and was treated with zoledronic acid for osteoporosis. A detailed ophthalmologic medical history should be taken for patients who will be prescribed zoledronic acid. Additionally, recent bisphosphonate use should be questioned in patients presenting with symptoms of uveitis. Clinicians should warn patients about symptoms that may develop related to uveitis, which is a very rare but serious side effect of bisphosphonates and should promptly evaluate patients by an ophthalmologist when any symptoms develop.